(untitled) (Communications in Mathematical Research, 2021)
Let T_n be the algebra of all n × n complex upper triangular matrices. We give the concrete forms of linear injective maps on T_n which preserve the nonzero idempotency of either products of two matrices or triple Jordan products of two matrices.